2022
DOI: 10.3390/agronomy12102482
|View full text |Cite
|
Sign up to set email alerts
|

A Real-Time Detection Algorithm for Sweet Cherry Fruit Maturity Based on YOLOX in the Natural Environment

Abstract: Fast, accurate, and non-destructive large-scale detection of sweet cherry ripeness is the key to determining the optimal harvesting period and accurate grading by ripeness. Due to the complexity and variability of the orchard environment and the multi-scale, obscured, and even overlapping fruit, there are still problems of low detection accuracy even using the mainstream algorithm YOLOX in the absence of a large amount of tagging data. In this paper, we proposed an improved YOLOX target detection algorithm to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Although image classification methods based on convolutional networks can achieve fruit maturity grading, they are generally suitable for individual maturity grading and not suitable for group target grading containing fruits of different maturity levels [ 9 ]. Previous studies have demonstrated the feasibility of using object detection methods for fruit maturity grading and counting [ 13 , 49 ]. Some studies have also used YOLO series algorithms for fruit maturity grading, but most have used YOLOv3, YOLOv4, or YOLOv5 [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although image classification methods based on convolutional networks can achieve fruit maturity grading, they are generally suitable for individual maturity grading and not suitable for group target grading containing fruits of different maturity levels [ 9 ]. Previous studies have demonstrated the feasibility of using object detection methods for fruit maturity grading and counting [ 13 , 49 ]. Some studies have also used YOLO series algorithms for fruit maturity grading, but most have used YOLOv3, YOLOv4, or YOLOv5 [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, relevant studies have proved that transfer learning can help improve the reliability of tomato maturity detection model [ 48 ]. The authors of [ 49 ] proposed a cherry maturity detection model based on YOLOX-EIoU-CBAM, with an mAP of 81.1%.…”
Section: Introductionmentioning
confidence: 99%
“…Through different periods of development, many versions of YOLO have appeared, and YOLOX [33] has a more rational network structure and better robustness compared to YOLOv3 in 2018 and YOLOv5 in 2020. Currently YOLOX in the field of target detection has made a breakthrough through various ways [34][35][36][37]. The whole YOLOX network can be divided into three parts, which are the backbone feature extraction network, strengthen feature extraction network, and the classification and regression part.…”
Section: Improvement Of Backbone Network Feature Output Layermentioning
confidence: 99%
“…As a result, the YOLOv4 model was improved to form the YOLO-Banana model, and the average accuracy (AP) of banana string and banana stem was 98.4% and 85.98%, respectively. Li et al [31] improved the YOLOX model by modifying the loss function and adding attention to detect sweet cherries and achieved a detection accuracy of 84.96%, an improvement of 2.34% relative to the initial YOLOX model. Wang and He [32] detected young apple fruits based on the YOLOv5 model with channel pruning, and the detection accuracy reached 95.80% with an average detection time of 8 milliseconds per image.…”
Section: Introductionmentioning
confidence: 99%